Today a woman went mad in the supermarket : stories - Wolitzer, Hilma (Bloomsbury Publishing, 2021)
"The uncannily relevant, deliciously clear-eyed collected stories of a critically acclaimed, award-winning "American literary treasure" (Boston Globe), ripe for rediscovery--with a foreword by Elizabeth Strout. From her many well-loved novels, Hilma Wolitzer--now 90 years old and at the top of her game--has gained a reputation as one of our best fiction writers, who "raises ordinary people and everyday occurrences to a new height." (Washington Post) These collected short stories--most of them originally published in magazines including Esquire and The Saturday Evening Post in the 1960s and 1970s, along with a new story that brings her early characters into the present--are evocative of an era that still resonates deeply today. In the title story, a bystander tries to soothe a woman who seems to have cracked under the pressures of motherhood. And in several linked stories throughout, the relationship between the narrator and her husband unfolds in telling and often hilarious vignettes. Of their time and yet timeless, Wolitzer's stories zero in on the domestic sphere and ordinary life with wit, candor, grace, and an acutely observant eye. Brilliantly capturing the tensions and contradictions of daily life, Today a Woman Went Mad in the Supermarket is full of heart and insight, providing a lens into a world that was often unseen at the time, and often overlooked now--reintroducing a beloved writer to be embraced by a whole new generation of readers"--